Legal Aspects Of Execution Of Dependent Rights Against Auction Buyers In Indonesia - Tarmizi Nugraha; Guntur Simamora (International Asia Of Law and Money Laundering (IAML), 2022)
The right of mortgage arises because of an agreement, that is, an agreement between the parties. Legal protection of the winner of the auction means the existence of legal certainty over the rights of the buyer / winner of the auction on the object purchased through the auction. In the auction process that has been carried out in practice will cause legal consequences, namely the transfer of the rights of the auction object from the seller to the buyer/winner of the auction as regulated in law no. 4 Of 1996 On The Rights Of Dependents On Land And Objects Related To The Land. In the transition of the rights of the auction object is not uncommon to cause a problem, such as the inability to control the auction object by the buyer/winner of the auction, which the owner of the auction object does not want to voluntarily vacate the auction object.